Analisis Prospek Dan Upaya Pengembangan Destinasi Wisata Pada Desa Maitara Kota Tidore Kepulauan Maluku Utara - Usman, Idham S.; Hasyim, Abdul Wahab; Sabuhari, Rahmat (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2023)
The purposes of this research are 1) To find out the development of tourism potential on Maitara Island, Tidore City Islands; 2) To find out the prospects for the development of a tourist area on the island of Maitara, City of Tidore Islands. The sample in this study consisted of two types of samples, namely: regional samples and tourist samples. Percentage analysis was carried out using percentage calculations, the analytical techniques to be used were questionnaires, direct interviews, field observations, personal documents and official documents. The data is processed through a SWOT analysis. The results of the study show: that the Kailupa tourist attraction (one thousand money) is in the Quadrant I position, which means it still has a